Current Status, Challenges, and Solution for Heart Transplantation in Public Sector Hospital - Pratik Manek; Ashish Madkaiker; Hemang Gandhi; Visharad Trivedi; Jayesh Prajapati; Anil Jain; Kartik Patel; Sunil Ninama; Venkata Mukunda; Himani Pandya; Chirag Doshi (Indian Journal of Transplantation)
For patients with end-stage cardiac failure, heart transplantation is still a lifesaving surgery; however, access to this treatment in public institutions faces many obstacles. This review article examines the status of heart transplantation in public institutions, including its difficulties and possible remedies. This review also examines the various obstacles faced by public sector hospitals when performing heart transplant procedures, including financial aspects, infrastructure, legal procedures, trained personnel and transplant teams, and logistical difficulties related to organ procurement and distribution. In conclusion, even though heart transplantation in public hospitals has many difficulties, systematic efforts to remove obstacles and provide creative fixes have the potential to improve the results and accessibility for patients in need of this lifesaving procedure.